Heterologous Wharton's Jelly Derived Mesenchymal Stem Cells Application on a Large Chronic Skin Wound in a 6-Month-Old Filly - Lanci, Aliai; Merlo, Barbara; Mariella, Jole; Castagnetti, Carolina; Iacono, Eleonora (Frontiers in Veterinary Science, 2019)
A complex feedback of growth factors, secreted by a variety of cell types, is responsible for the mediation of skin healing. Despite the recent advances in wound healing management, this fails up to 50% and skin wounds can still be considered one of the main causes of morbidity, both in human and veterinary medicine. Regenerative medicine, involving mesenchymal stromal cells (MSCs), is nowadays a promising solution for skin wound healing. Indeed, MSCs are involved in the modulation of the inflammatory local response and cell replacing, by a paracrine mode of action. Local application of equine umbilical cord Wharton’s jelly MSCs (WJMSCS) was carried out in a 6-months-old filly with a non-healing skin wound. Heterologous WJMSCs were applied four times using a carboxymethylcellulose (CMC) gel, produced dissolving CMC in autologous plasma. At first application the mean wound area was 7.28±0.2 cm2. Four days after the last application of WJMSCs, the mean wound area was 1.90±0.03 cm2, and the wound regression rate was +74%. No local or systemic side effects were registered after WJMSCs application and no evident exuberant scar was observed after wound healing. At discharge, the mean wound area was 0.38±0.01 cm2 and the total regression rate was +80%. Five days later, the wound was completely healed. In the present clinical case report, the use of WJMSCs led to promising clinical results, paving the way for possible future applications in the treatment of chronic wounds in horses.